Analytical chemistry 4 : plenary lectures presented at the International Congress on Analytical Chemistry held at Kyoto, Japan 3-7 April 1972 - Senda, Mitsugi, 1929- (Butterworths, 1973)
Analytical Chemistry - 4 is a collection of plenary lectures presented at the International Congress on Analytical Chemistry, held in Kyoto, Japan on April 3-7, 1972. This book contains 11 chapters and begins with a summary of the kinetics of complex formation of metals with organic ligands in analytical chemistry. The subsequent chapters deal with the chelate compounds; the concepts of trace analysis; the developments in quantitative organic ultramicro elementary analysis; and the status of radiochemistry and its application to activation analysis. These topics are followed by presentation o.